2011
DOI: 10.1002/bit.24385
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up and integration of alkaline hydrogen peroxide pretreatment, enzymatic hydrolysis, and ethanolic fermentation

Abstract: Alkaline hydrogen peroxide (AHP) has several attractive features as a pretreatment in the lignocellulosic biomass-to-ethanol pipeline. Here, the feasibility of scaling-up the AHP process and integrating it with enzymatic hydrolysis and fermentation was studied. Corn stover (1 kg) was subjected to AHP pretreatment, hydrolyzed enzymatically, and the resulting sugars fermented to ethanol. The AHP pretreatment was performed at 0.125 g H(2) O(2) /g biomass, 22°C, and atmospheric pressure for 48 h with periodic pH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 47 publications
4
66
0
1
Order By: Relevance
“…Upon analyzing the results from a one-way ANOVA test (available in the Additional file 1), it became apparent that neither response was significantly impacted by the solids loading during deacetylation, while the reaction time was a minor factor-the responses were largely driven by reaction temperature and the sodium hydroxide loading. We also found that in experiments conducted at sodium hydroxide loadings of less than 1.5 g/g acetate, the pH of the post-extraction liquor was consistently in a neutral range (6)(7)(8). This indicates that the sodium hydroxide is actually consumed in the reaction, rather than simply acting as a catalyst.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Upon analyzing the results from a one-way ANOVA test (available in the Additional file 1), it became apparent that neither response was significantly impacted by the solids loading during deacetylation, while the reaction time was a minor factor-the responses were largely driven by reaction temperature and the sodium hydroxide loading. We also found that in experiments conducted at sodium hydroxide loadings of less than 1.5 g/g acetate, the pH of the post-extraction liquor was consistently in a neutral range (6)(7)(8). This indicates that the sodium hydroxide is actually consumed in the reaction, rather than simply acting as a catalyst.…”
Section: Resultsmentioning
confidence: 63%
“…Other processes have been explored that use neutral, ionic liquids or alkaline chemistry, including hydrothermal pretreatment [5], ionic liquid pretreatment using imidazole [6], peroxide pretreatment, oxidative lime pretreatment, and pulping-like sodium hydroxide pretreatments [7][8][9][10][11][12][13][14][15]. However, these processes are typically intended to function as a stand-alone pretreatment, and the severity of the process is increased to enable effective enzymatic hydrolysis with no further processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline hydrogen peroxide (AHP) pretreatment is one such approach that has been studied since the 1980s [6][7][8]. AHP results in significant improvement in the enzymatic digestibility of commelinid monocots including corn stover and wheat straw [9,10] and can generate hydrolysates with more than 100 g/L of monomeric sugars that are fermentable without detoxification (manuscript in preparation). The mechanisms by which AHP pretreatment reduces recalcitrance include the fragmentation and solubilization of ester-linked xylan and lignin [11,12], as well as the oxidation, solubilization, and at high H 2 O 2 loadings, mineralization of lignin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Esse pré-tratamento adicional tem como objetivo principal promover a deslignificação da biomassa [16].…”
unclassified